Nyctomyia, a replacement name for the preoccupied genus Nyx Harbach & Linton, 2013 (Diptera: Culicidae) - Harbach, Ralph E. (Zootaxa, 2013)
Harbach et al. (2013) proposed the new generic name Nyx for an undescribed cavernicolous species of Culicidae discovered in a cave at Wat Tham Panthurat in Surat Thani Province of southern Thailand. The authors were not aware that the generic name was already in use for a genus in the lepidopteran family Choreutidae (Heppner, 1982). In accordance with Article 60 of the International Code of Zoological Nomenclature (ICZN, 1999), Nyx Heppner, 1982, has priority and Nyx Harbach & Linton, 2013, must be treated as its junior homonym. Hence, I herewith propose the replacement name Nyctomyia nom. nov. for Nyx Harbach & Linton, 2013. The generic name is derived from the name of the Greek goddess Nyx (nominative, transliteration of νύξ; genitive Nyctos, transliteration of νυκτός, genitive stem Nycto-) and the Greek noun myia (transliteration of mυῖα, f. fly), literally translated as “Nyx fly”. The two-letter abbreviation Nc. is recommended for Nyctomyia. Nyctomyia pholeocola (Linton & Harbach) comb. nov. is the only species included in the genus.